Tantangan Ideologi Pancasila Di Era Media Sosial: Analisis Pengaruh Polarisasi Digital terhadap Persatuan Bangsa - Welan, Alfonsa Ema; Kampas, Emiliana (Jurnal Pendidikan Kewarganegaraan dan Politik, 2025)
In the digital era, social media has transformed the way information is produced, distributed, dan consumed, thereby posing new challenges to Pancasila as the ideological foundation dan unifying force of the Indonesian nation. The high level of internet dan social media penetration, with 73.8% of the population connected to the internet dan 68.9% actively using social media, increases the risk of digital polarization through echo chambers, disinformation, dan algorithmic curation. This study aims to analyze the challenges faced by Pancasila in the context of digital polarization dan to examine its implications for national unity. The research adopts a qualitative approach using a literature review design by critically examining scholarly journal articles, academic books, policy reports, dan relevant research documents. The findings indicate a gap in the internalization of Pancasila values, particularly among younger generations who are strongly influenced by social media algorithms. Digital polarization contributes to identity fragmentation, rising intolerance, dan declining quality of public dialogue, which negatively affects social cohesion dan deliberative practices. Moreover, algorithmic curation that prioritizes emotional content over critical narratives further narrows the space for cross group deliberation. The study concludes that challenges to Pancasila do not stem from weaknesses in its ideological values, but rather from changes in the digital information ecosystem that shape new patterns of social interaction. Therefore, strengthening digital literacy integrated with value education, community based interventions, dan transparent governance of social media platforms are essential strategies to reduce digital polarization dan reinforce national unity.